2017
DOI: 10.3390/membranes7030045
|View full text |Cite
|
Sign up to set email alerts
|

Breath-Figure Self-Assembly, a Versatile Method of Manufacturing Membranes and Porous Structures: Physical, Chemical and Technological Aspects

Abstract: The review is devoted to the physical, chemical, and technological aspects of the breath-figure self-assembly process. The main stages of the process and impact of the polymer architecture and physical parameters of breath-figure self-assembly on the eventual pattern are covered. The review is focused on the hierarchy of spatial and temporal scales inherent to breath-figure self-assembly. Multi-scale patterns arising from the process are addressed. The characteristic spatial lateral scales of patterns vary fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 191 publications
(359 reference statements)
5
69
0
Order By: Relevance
“…This methodology is a widely employed strategy and several reviews have been recently reported covering both the chemical and physical aspects of porous film formation. [10][11][12]15] In terms of applications, porous films obtained using the Breath Figures methodology have the potential to be employed in tissue engineering applications since they can either 6 support cell adhesion and proliferation [16][17][18][19][20][21][22][23][24][25][26][27][28][29] or exactly the opposite, i.e. improve the adhesion and act as barriers.…”
Section: Fabrication Of Biocompatible and Efficient Antimicrobial Pormentioning
confidence: 99%
“…This methodology is a widely employed strategy and several reviews have been recently reported covering both the chemical and physical aspects of porous film formation. [10][11][12]15] In terms of applications, porous films obtained using the Breath Figures methodology have the potential to be employed in tissue engineering applications since they can either 6 support cell adhesion and proliferation [16][17][18][19][20][21][22][23][24][25][26][27][28][29] or exactly the opposite, i.e. improve the adhesion and act as barriers.…”
Section: Fabrication Of Biocompatible and Efficient Antimicrobial Pormentioning
confidence: 99%
“…Instead of forming concentric rings for the substrate temperature larger than or equal to 30°C, surface patterns consisting of 'hole-network' were formed. The formation of these surface patterns can be attributed to the Sun and Yang -eXPRESS Polymer Letters Vol.12, No.8 (2018) 'Breath Figure' phenomenon [41], which usually occurs during the condensation of water droplets onto the surface of a polymer solution with a volatile solvent in a high humidity environment. The evaporation of the volatile solvent in the polymer solution causes the decrease of local temperature, leading to the formation of water micro-droplets and the penetration of the water micro-droplets onto the layer of the polymer solution.…”
Section: Effect Of Substrate Temperaturementioning
confidence: 99%
“…One of the simplest and most effective methods enabling manufacturing microporous surfaces is the so-called breath-figures self-assembly method [12][13][14][15][16][17]. Breathfigures process is a commonly observed phenomenon in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…especially suitable for the drop-casting process, resulting in the breath-figures selfassembly[12][13][14][15][16][17]. The drop-casting of polystyrene dissolved in the chlorinated solvents on the silicone oil-lubricated glass slides, carried out in the humid atmosphere, gave rise to hierarchical topographies built of micro-and nano-pores.…”
mentioning
confidence: 99%